Factors influencing operative time for mini-endoscopic combined intrarenal surgery for renal stones - Hiroki Ito; Tetsuo Fukuda; Fukashi Yamamichi; Takahiko Watanabe; Yosuke Shibata; Tadashi Tabei; Takaaki Inoue; Junichi Matsuzaki; Kazuki Kobayashi (Scientific Reports)
Abstract Mini-endoscopic combined intrarenal surgery (ECIRS) offers improved advantages in the treatment of renal stones. However, the factors influencing the operative time remain poorly understood. This study aimed to identify the factors that enhance treatment planning and minimize complications. Clinical data from consecutive patients who underwent mini-ECIRS for renal stones and achieved a stone-free status between 2015 and 2021 at three high-volume centers in Japan were analyzed. The final treatment outcome was evaluated by computed tomography imaging at postoperative 1 month, and a successful outcome was defined as complete stone-free or residual stone fragments < 4 mm. Logistic and linear regression models were used to predict the operative duration of mini-ECIRS. An operative time of ≥ 120 min was significantly associated with punctured pole and body mass index (BMI), and septic shock was only observed in patients with operative times of ≥ 120 min. The multivariate model for the operative time for mini-ECIRS identified five clinical factors: punctured pole, number of stones, number of involved calyces, BMI, and preoperative nephrostomy. We believe these findings will help surgeons and patients plan suitable treatment strategies, predict the additional need for a second mini-ECIRS or retrograde intrarenal surgery alone, and avoid severe complications.